Estudo da influência do teor de CO2 na regularidade da transferência de metal e estabilidade do processo MIG/MAG - Liskevych, Olga (2010)
GMAW process has been widely used in the industry. The shilding atmosphere is one of the most important variables in this process since it can influence the arc formation, metal transfer, geometry and bead appearance. CO2 blended with Ar is the most common shielding gas used for short-circuit GMAW (the most popular transfer mode). However, there is still lack of more scientific data to explain the performance of the mixtures. This paper presents a systematic study of the influence that CO2 content in mixture with Argon has on the operational performance of the short-circuit GMAW. The objective of this study was to describe, to quantify and to explain the alterations in the metal transfer behavior, spatter generation, weld bead geometry and bead finish due to the different CO2 contents in the shielding gas. Carbon steel plates were welded in adequate parametric conditions for each CO2+Ar shielding gas composition (CO2 ranging from 2% to 100%). These conditions were found by applying a metal transfer regularity index over welds carried out at different setting voltages for each gas blend. A target of 130 A was applied as base for comparison. Laser shadowgrafy with high speed filming and current and voltage oscillograms were used as analysis tools. The results showed (and confirmed) that the increase of the CO2 content deteriorates metal transfer regularity, leading to excessive spatter generation and uneven bead appearance, but increases the penetration and the fusion area of the weld beads and improve bead convexity. In general, the CO2 content should neither be lower than 10% nor higher than 30%, unless for thin plates.